Breastfeeding and complementary feeding associated with body composition in 18–19 years old adolescents in the 1993 Pelotas Birth Cohort - Orlandi, Silvana Paiva (BMC Nutr, 2017)
BACKGROUND: The first years of life are critical for human development, therefore it is important to investigate early factors that may influence the development of body composition later in life. In this study, we aimed to evaluate the association between breastfeeding duration and age of introduction of complementary feeding with body composition at 18–19 years. METHODS: This is a prospective study conducted with adolescents belonging to the 1993 Pelotas Birth Cohort. Duration of breastfeeding, age of introduction of other types of milk and complementary feeding were obtained from a subsample of this cohort periodically monitored during the first year of life. The fat mass (FM) and fat-free mass (FFM) indices were estimated using plethysmography (BOD POD ™). Crude and adjusted analyses were stratified by sex using a linear regression model. RESULTS: 1438 adolescents (694 boys and 744 girls) had complete information on exposures and outcomes.. Among men, the mean FMI and FFMI were 4.0 ± 3.1 kg / m(2) and 19.0 ± 1.9 kg / m(2); and among women, 8.0 ± 3.2 kg / m(2) and 15.5 ± 1.7 kg / m(2), respectively. Neither breastfeeding duration nor age of introduction of complementary foods was associated with mean FMI in both sexes. Mean FFMI was higher among women who were breastfed for three months or more and among men who were breastfed for six months or more. Women who started the complementary feeding after five months of age had lower mean FFMI in adolescence. CONCLUSION: The data suggest that only mean FFM in adolescence is associated with early feeding behaviors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40795-017-0201-z) contains supplementary material, which is available to authorized users.